HUBUNGAN POLA ASUH ORANG TUA DENGAN PRESTASI BELAJAR MATEMATIKA ANAK USIA SEKOLAH PADA SEMESTER GENAP DI SEKOLAH DASAR NEGERI 1 GUNUNGSARI - Putu Windi Ridayanti; Kadek Devy Marleni (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2018)
Background:This study aimed to determine the parents toward children pre school learning achievement on second semester sdn 1 gunungsari. Method:This research used descriptive corelational with cross-sectional design. This research conducted in SD Negeri 1 Gunungsari, Seririt District, BulelengRegency, Bali Province by the number of respondents as many as 61 students were selected by purposive sampling. Collecting data in this study by using a questionnaire to measure variables parenting parents and observation UAS value of mathematics to measure variables mathematics achievement school-age children in SDN 1 Gunungsari. Result:Based on research conducted found that: 1) the parents of students who have positive (Democratic) parenting that as many as 49 people (80,3%), and negative (authoritarian, permissive) parenting as many as 12 people (19,7%), 2) 14 students have a good learning performance, 39 students have learned quite a feat, and 8 students have learning achievement is less, and 3) Based on the analysis that has been done, get r count equal to 0.552 with significance or value of the probability p = 0.000 (0 <0.05) mean H0 rejected and Ha received, Conclusions:so it can be concluded that there is a significant correlation parenting parents toward children pre school learning achievement on second semester SDN 1 Gunungsari. So that parenting parents should do well, so that students' mathematics achievement can be increased to the optimum.